[3+2] cycloaddition reaction of metallacyclopropene with nitrosonium ion: isolation of aromatic metallaisoxazole. Issue 50 (20th May 2020) - Luo, Ming; Sui, Yanheng; Lin, Xinlei; Zhu, Congqing; Yan, Zhewei; Ruan, Yonghong; Zhang, Hong; Xia, Haiping
Abstract : The [3+2] cycloaddition of metallacyclopropene with nitrosonium ion gives the first aromatic osmaisoxazole-fused osmapentalene. Abstract : The synthesis of metallaisoxazole by the [3+2] cycloaddition reaction of metallacyclopropene with nitrosonium tetra-fluoroborate has been achieved under mild conditions. Nuclear magnetic resonance spectra, X-ray crystallographic analysis, and density functional theory calculations all suggest that the metallaisoxazole exhibits an aromatic character.